Procesos operativos en la policía judicial de la unidad de vigilancia comunitaria de Babahoyo, en el período 2024. - Rodríguez Quispe, Katherine Gabriela (2024)
Operational processes are internal activities of the institution to provide users with relevant attention in all processes with the optimization of resources. The Judicial Police is the unit in charge of investigating crimes, collecting evidence and supporting the justice system in the prosecution of crime. Its operational processes seek to guarantee efficiency, transparency and legality in the resolution of cases. The investigation originates within the judicial police department in the Babahoyo community surveillance unit, with the objective of analyzing the internal operational processes that lead to optimizing user attention at the time of filing a complaint until responding to the institution's protocol procedures.